2022
DOI: 10.1080/07853890.2022.2098375
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized clinical trial of active-fluidics versus gravity-fluidics system in phacoemulsification for age-related cataract (AGSPC)

Abstract: Background To figure out the efficacy, effects, safety and patient’s subjective perceptions of phacoemulsification with the active-fluidics system (AFS). Patients and methods This was a prospective, randomized, double-masked, controlled clinical study. Age-related cataract patients were recruited and randomly assigned to the AFS group and gravity-fluidics system (GFS) group in a ratio of 1:1 to have phacoemulsification. Participants were followed up at one day, one week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…The effect of PKE on retinal structure and function has also been the focus of recent research. Increases in retinal thickness (RT) and retinal vessel density (VD) after PKE have been observed, and such changes are closely related to surgical injuries, IOP changes and inflammatory reactions [ 30 , 31 , 42 , 43 , 44 ]. Comparisons between the AFS and GFS on this topic may reveal some potential mechanisms.…”
Section: Performance Of Afs In Pkementioning
confidence: 99%
See 4 more Smart Citations
“…The effect of PKE on retinal structure and function has also been the focus of recent research. Increases in retinal thickness (RT) and retinal vessel density (VD) after PKE have been observed, and such changes are closely related to surgical injuries, IOP changes and inflammatory reactions [ 30 , 31 , 42 , 43 , 44 ]. Comparisons between the AFS and GFS on this topic may reveal some potential mechanisms.…”
Section: Performance Of Afs In Pkementioning
confidence: 99%
“…No significant difference has been yet reported between the AFS and GFS in terms of other surgical complications. Randomized controlled studies reported no significant difference in the incidence of adverse events such as allergic conjunctivitis, ocular congestion, dry eye, and posterior vitreous detachment after PKE with each of the two fluidics systems, and none had other serious complications [ 7 , 29 , 31 ].…”
Section: Performance Of Afs In Pkementioning
confidence: 99%
See 3 more Smart Citations